Features of development of coordinating capabilities of badminton players on the stage of prior basic training - Шиян [Vladimir Shiyan], Володимир Миколайович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Еxperimental material in relation to the study of level of development of coordinating capabilities of the badminton players being on the stage of preliminary base preparation is presented. The research target consisted in the decision of features of development of coordinating capabilities of badminton players 12–14 years. As research methods were used: analysis and generalization of literary sources; pedagogical testing; pedagogical experiment; methods of mathematical statistics. It is set, that in badminton, take the first place exactly to the coordinating capabilities. On the most indexes, both at boys, and at girlies the meaningful differences are exposed statistically in the age period 12–13 and 13–14 years. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->